Cosmic Antiproton Sensitivity for the GAPS Experiment - Rogers, F.; Aramaki, T.; Bird, R.; Boezio, M.; Boggs, S. E.; Bonvicini, V.; Campana, D.; Craig, W. W.; Everson, E.; Fabris, L.; Fuke, H.; Gahbauer, F.; et al. (Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021), 2022)
The General Antiparticle Spectrometer (GAPS) experiment is a balloon payload designed to measure low-energy cosmic antinuclei during at least three ∼ 35-day Antarctic flights, with the first flight planned for December, 2022. With its large geometric acceptance and novel exotic atom-based particle identification method, GAPS will detect ∼ 1000 antiprotons per flight, producing a precision cosmic antiproton spectrum in the kinetic energy range of 0.03−0.23 GeV/n at float altitude (corresponding to 0.085−0.30 GeV/n at the top of the atmosphere). With these high statistics in a measurement extending to lower energy than any previous experiment, and with orthogonal sources of systematic uncertainty compared to measurements made using traditional magnetic spectrometer techniques, the GAPS antiproton measurement will be sensitive to physics including dark matter annihilation, primordial black hole evaporation, and cosmic ray propagation. The antiproton measurement will also validate the GAPS exotic atom technique for the antideuteron and antihelium rare-event searches and provide insight into models of cosmic particle attenuation and production in the atmosphere. This contribution demonstrates the GAPS sensitivity to antiprotons using a full instrument simulation, event reconstruction, and solar and atmospheric effects.